Institutional roles, structures, funding and research partnerships towards evidence-informed policy-making: a multisector survey among policy-makers in Nigeria - Chigozie Jesse Uneke; Ijeoma Nkem Okedo‑Alex; Ifeyinwa Chizoba Akamike; Bilikis Iyabo Uneke; Irene Ifeyinwa Eze; Onyekachi Echefu Chukwu; Kingsley Igboji Otubo; Henry C. Urochukwu (BMC, 2023)
Abstract Background Evidence-informed policy-making aims to ensure that the best and most relevant evidence is systematically generated and used for policy-making. The aim of this study was to assess institutional structures, funding, policy-maker perspectives on researcher-policy-maker interactions and the use of research evidence in policy-making in five states in Nigeria. Methods This was a cross-sectional study carried out among 209 participants from two geopolitical zones in Nigeria. Study participants included programme officers/secretaries, managers/department/facility heads and state coordinators/directors/presidents/chairpersons in various ministries and the National Assembly. A pretested semi-structured self-administered questionnaire on a five-point Likert scale was used to collect information on institutional structures for policy and policy-making in participants' organizations, the use of research evidence in policy and policy-making processes, and the status of funding for policy-relevant research in the participants' organizations. Data were analysed using IBM SPSS version 20 software. Results The majority of the respondents were older than 45 years (73.2%), were male (63.2) and had spent 5 years or less (74.6%) in their present position. The majority of the respondents' organizations had a policy in place on research involving all key stakeholders (63.6%), integration of stakeholders' views within the policy on research (58.9%) and a forum to coordinate the setting of research priorities (61.2%). A high mean score of 3.26 was found for the use of routine data generated from within the participants' organizations. Funding for policy-relevant research was captured in the budget (mean = 3.47) but was inadequate (mean = 2.53) and mostly donor-driven (mean = 3.64). Funding approval and release/access processes were also reported to be cumbersome, with mean scores of 3.74 and 3.89, respectively. The results showed that capacity existed among career policy-makers and the Department of Planning, Research and Statistics to advocate for internal funds (mean = 3.55) and to attract external funds such as grants (3.76) for policy-relevant research. Interaction as part of the priority-setting process (mean = 3.01) was the most highly rated form of policy-maker-researcher interaction, while long-term partnerships with researchers (mean = 2.61) had the lower mean score. The agreement that involving policy-makers in the planning and execution of programmes could enhance the evidence-to-policy process had the highest score (mean = 4.40). Conclusion The study revealed that although institutional structures such as institutional policies, fora and stakeholder engagement existed in the organizations studied, there was suboptimal use of evidence obtained from research initiated by both internal and external researchers. Organizations surveyed had budget lines for research, but this funding was depicted as inadequate. There was suboptimal actual participation of policy-makers in the co-creation, production and dissemination of evidence. The implementation of contextually relevant and sustained mutual institutional policy-maker-researcher engagement approaches is needed to promote evidence-informed policy-making. Thus there is a need for institutional prioritization and commitment to research evidence generation.